Advocate Role Against Clients in Handling Follow-Up Cases Corruption Crime - Vicki Dwi Purnomo; Aida Dewi (PT FORMOSA CENDEKIA GLOBAL, 2023)
Advocates must have high human character, be honest, fair and responsible. In the code of ethics for the Advocate profession and Law Number 18 of 2003 concerning Advocates there is a section which states that advocates must keep everything known from their clients, both good and bad. So it's up to the individual advocate to determine the attitude of his conscience. This research is included in the category of library research or library research with data obtained from literature study activities. refers to normative studies. This study refers to literature research using descriptive-comparative-analytic. So to present the results of this study will be described which is then focused on the issues raised